2015
DOI: 10.1111/hae.12832
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous bilateral total knee arthroplasty in patients with haemophilia: a safe and cost‐effective procedure?

Abstract: Simultaneous bilateral TKA seems to be a safe and cost-effective approach without increasing the rate of complications in patients' bilateral haemophilic knee arthropathy. The procedure is, at least, as effective as staged unilateral knee arthroplasty in improving the patients' quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…In previous studies, the five- and ten-year prosthetic survival rates were approximately 90% for TKA surgery in HA patients 24 , 25 , which is similar to the results of our study. We experienced a total of 3 revisions in the mean follow-up of 6 years among 54 prostheses, for a revision rate of 5.6%.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In previous studies, the five- and ten-year prosthetic survival rates were approximately 90% for TKA surgery in HA patients 24 , 25 , which is similar to the results of our study. We experienced a total of 3 revisions in the mean follow-up of 6 years among 54 prostheses, for a revision rate of 5.6%.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have reported no difference in improvement of joint function between simultaneous and staged bilateral or unilateral TKA 21 , 23 , 25 . Our results were consistent with these studies.…”
Section: Discussionmentioning
confidence: 70%
“…These findings seem to imply that simultaneous multiple joint replacement for patients with HA would lead to higher risks compared with single joint replacement. On the contrary, Mortazavi et al [ 13 ] compared the prognosis of 8 patients who underwent simultaneous bilateral TKA and 19 patients who underwent unilateral TKA and concluded that simultaneous bilateral TKA is a safe and cost-effective approach without augmenting the incidence of complications in patients with hemophilia. Thes et al [ 14 ] conducted a retrospective case–control study and found that simultaneous bilateral TKA is associated with significantly lower costs of coagulation factors and longer hospital stay compared with staged bilateral TKA, but no significant difference in clinical outcome was noted.…”
Section: Discussionmentioning
confidence: 99%
“…Many patients with hemophilia suffer from end-stage arthropathy involving multiple joints 2,5,6,15 . There has been a trend to perform multiple surgical procedures during a single operating session for patients with hemophilia when surgical intervention has been indicated 9,16 . Because a major fraction of the financial burden of surgical treatment for patients with hemophilia is the cost of factor replacement, the benefits of multiple procedures in patients with hemophilia are twofold.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple joint procedures are defined as any combination of major surgical procedures for the treatment of end-stage arthropathy in patients with hemophilia (including total knee arthroplasty, total hip arthroplasty, and ankle arthrodesis) during a single anesthetic episode. In some studies, simultaneous bilateral total knee arthroplasty has been proposed for patients with hemophilia as a way to reduce costs, improve rehabilitation, and accelerate the return to normal life 7-9 . Multiple joint procedures also can reduce the event of intensive treatment with clotting factor concentrate compared with staged single joint procedures.…”
mentioning
confidence: 99%